Information Seeking Anxiety Amongst Postgraduate Students of Punjab Agricultural University, Ludhiana - Bala, Suniti; Chandwani, Sanjay; Singh, Nirmal; Kumar, Dhiraj (DESIDOC Journal of Library & Information Technology, 2023)
This paper is envisioned to investigate the Information Seeking Anxiety (ISA) among postgraduate (masters’ and PhD) students of Punjab Agricultural University, Ludhiana. The Information Seeking Anxiety Scale (ISAS) developed by Erfanmanesh, et al., containing 47 statements representing ISA under seven components having Cronbach alpha values reported to be at 0.902, was used as a data collection tool. 108 students participated in the survey. About 70 % respondents experienced mild level of anxiety. The gender-based difference in ISA associated with ‘Computer and the Internet’ was found to be significant at .05 (t= 2,426), females being less anxious. The location of the students did not influence their ISA, and different components of the ISAS were found to be interrelated, affecting the overall anxiety level. Prevalence of low to severe levels of ISA amongst students mandated the need for planning and execution of well-prepared information literacy programmes.